At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To differentiate the function [tex]\( f(x) = (x^4 - 1)(x - 1) \)[/tex] using the product rule, we will follow these steps systematically:
1. Identify the functions: Let [tex]\( u(x) = x^4 - 1 \)[/tex] and [tex]\( v(x) = x - 1 \)[/tex].
2. Differentiate each function:
- The derivative of [tex]\( u(x) \)[/tex] with respect to [tex]\( x \)[/tex] is [tex]\( u'(x) = 4x^3 \)[/tex].
- The derivative of [tex]\( v(x) \)[/tex] with respect to [tex]\( x \)[/tex] is [tex]\( v'(x) = 1 \)[/tex].
3. Apply the product rule: The product rule states that if [tex]\( f(x) = u(x)v(x) \)[/tex], then the derivative [tex]\( f'(x) \)[/tex] is given by:
[tex]\[ f'(x) = u'(x)v(x) + u(x)v'(x) \][/tex]
4. Plug in the differentiated functions and the original functions:
- Substitute [tex]\( u'(x) = 4x^3 \)[/tex], [tex]\( u(x) = x^4 - 1 \)[/tex], [tex]\( v'(x) = 1 \)[/tex], and [tex]\( v(x) = x - 1 \)[/tex] into the product rule formula:
[tex]\[ f'(x) = 4x^3 (x - 1) + (x^4 - 1)(1) \][/tex]
5. Simplify the expression:
[tex]\[ f'(x) = 4x^3 (x - 1) + x^4 - 1 \][/tex]
[tex]\[ f'(x) = 4x^4 - 4x^3 + x^4 - 1 \][/tex]
6. Combine like terms:
[tex]\[ f'(x) = x^4 + 4x^3 (x - 1) - 1 \][/tex]
Therefore, the derivative of [tex]\( f(x) = (x^4 - 1)(x - 1) \)[/tex] with respect to [tex]\( x \)[/tex] is
[tex]\[ f'(x) = x^4 + 4x^3 (x - 1) - 1 \][/tex]
1. Identify the functions: Let [tex]\( u(x) = x^4 - 1 \)[/tex] and [tex]\( v(x) = x - 1 \)[/tex].
2. Differentiate each function:
- The derivative of [tex]\( u(x) \)[/tex] with respect to [tex]\( x \)[/tex] is [tex]\( u'(x) = 4x^3 \)[/tex].
- The derivative of [tex]\( v(x) \)[/tex] with respect to [tex]\( x \)[/tex] is [tex]\( v'(x) = 1 \)[/tex].
3. Apply the product rule: The product rule states that if [tex]\( f(x) = u(x)v(x) \)[/tex], then the derivative [tex]\( f'(x) \)[/tex] is given by:
[tex]\[ f'(x) = u'(x)v(x) + u(x)v'(x) \][/tex]
4. Plug in the differentiated functions and the original functions:
- Substitute [tex]\( u'(x) = 4x^3 \)[/tex], [tex]\( u(x) = x^4 - 1 \)[/tex], [tex]\( v'(x) = 1 \)[/tex], and [tex]\( v(x) = x - 1 \)[/tex] into the product rule formula:
[tex]\[ f'(x) = 4x^3 (x - 1) + (x^4 - 1)(1) \][/tex]
5. Simplify the expression:
[tex]\[ f'(x) = 4x^3 (x - 1) + x^4 - 1 \][/tex]
[tex]\[ f'(x) = 4x^4 - 4x^3 + x^4 - 1 \][/tex]
6. Combine like terms:
[tex]\[ f'(x) = x^4 + 4x^3 (x - 1) - 1 \][/tex]
Therefore, the derivative of [tex]\( f(x) = (x^4 - 1)(x - 1) \)[/tex] with respect to [tex]\( x \)[/tex] is
[tex]\[ f'(x) = x^4 + 4x^3 (x - 1) - 1 \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.